Strategic Business of Small-Scale Layer Chicken Farming in Ponggok District, Blitar Regency: A SWOT and IE Matrix Approach - Huwaina, Iyan Izazi; Baga, Lukman M.; Priatna, Wahyu Budi (Business Review and Case Studies, 2025)
Background: Animal husbandry is vital in Indonesia. On March 2, 2020, Indonesia confirmed its first COVID‑19 case. Mobility restrictions disrupted egg distribution in the Blitar District. The Ponggok Subdistrict, a key egg-production area, saw a sharp drop in output. Many poultry farmers have struggled because they continue to incur losses. In 2015, Ponggok had 1,151 poultry farmers. This number fell to 1,021 by 2021, mainly because of the COVID‑19 pandemic.Purpose: This study aims to formulate strategic recommendations to enhance the sustainability of smallholder chicken businesses in Ponggok District. This research involves an in-depth analysis of the agribusiness environment surrounding these enterprises, along with a thorough examination of both internal and external factors that influence their operations and viability. By carefully examining these dynamics, this study provides actionable insights and strategies that will not only support the longevity of these businesses, but also contribute to the overall prosperity of the agricultural sector within the region.Design/methodology/approach: This study was conducted from January to May 2022, utilizing both qualitative and quantitative data collection methods. Qualitative insights were gathered from in-depth interviews with five key stakeholders from the Blitar Regency Livestock and Fisheries Office, and 20 small-scale poultry farmers in Ponggok. The quantitative component involved structured surveys of the key stakeholders. The data analysis employed SWOT analysis and IE Matrix. Findings/Result: The analysis positioned small-scale laying chicken businesses in the "Hold and Maintain" quadrant of the IE Matrix. This indicates that these businesses are currently stable but require careful management to enhance their growth potential. Based on the findings of the SWOT Matrix, seven strategic alternatives were developed to guide their development and success. These strategies include enhancing collaboration among farmers, which can lead to the sharing of resources and knowledge; improving self-production of feed to reduce dependency on external suppliers; maintaining accurate financial records for better financial health; and strengthening the capacity of farmers through training and access to resources.Conclusion: Strategic interventions are critical for the sustainability of smallholder poultry farms, particularly in the aftermath of a crisis. By focusing on improving feed cost efficiency, which constitutes a significant expense for these businesses; promoting group-based operations to leverage collective bargaining and shared infrastructure; and implementing supportive policies that encourage growth and stability, we can significantly enhance the resilience and competitiveness of smallholder poultry farms. These efforts will not only support the farmers themselves but will also contribute to the region's overall food security and agricultural sustainability.Originality/value (State of the art): This study presents a strategic framework for sustaining smallholder layer chicken farms in the face of crisis impacts, utilizing a combined approach of IE Matrix and SWOT analysis in a post-COVID-19 context.Keywords: business strategy, livestock, laying hens, price fluctuations, SWOT